SATISFACTION OF CPNS LATSAR PARTICIPANTS DURING THE COVID-19 PANDEMIC AT THE HUMAN RESOURCES DEVELOPMENT CENTER REGIONAL BUKITTINGGI - Andari Dwi Utami (Sustainability (STPP) Theory, Practice and Policy, 2022)
This study examines the satisfaction of CPNS Latsar training during the Covid-19 pandemic at the Bukittinggi Regional Human Resources Development Center (PPSDM). The research method used in this study was a literature review with the topic of CPNS latsar training during the Covid-19 pandemic. The purpose of this study was to measure Latsar's training satisfaction. Information is obtained from official websites, academic articles and other sources deemed relevant. Based on this description, it can be concluded that the analysis of participant satisfaction greatly affects the training of latsar during the covid-19 period which is still less effective in carrying out online training.especially the Bukittinggi Regional PPSDM to be able to improve and increase participant satisfaction because this can support the success of the implementation of the latsar training organized by the Bukittinggi Regional PPSDM itself.And tolatsar training participants, in order to be able to read the training module that has been provided as a guide and be serious in participating in the latsar training in a more proactive way during discussions.